Submarginal drumlin formation and late Holocene history of Fláajökull, southeast Iceland - Jónsson, Sverrir A.; Benediktsson, Ívar Örn; Ingólfsson, Ólafur; Schomacker, Anders; Bergsdóttir, Helga Lucia; Jacobson Jr., William R.; Linderson, Hans (Annals of Glaciology, 2016)
Published version. Source at http://doi.org/10.1017/aog.2016.4 . License CC BY 4.0 . Fláajökull is a non-surging outlet glacier draining the south-eastern part of the Vatnajökull, southeast Iceland. Fláajökull was stationary or advanced slightly between 1966 and 1995 and formed a prominent end moraine. Glacial retreat since then has revealed a cluster of 15 drumlins. This study focuses on the morphology and sedimentology of the drumlins. They are 100–600 m long, 40–130 m wide, and have cores of glaciofluvial sediment or till. The drumlins are draped by ~1 m thick, massive subglacial traction till. The glacier forefield is characterized by a number of arcuate and saw-tooth, terminal and recessional moraine ridges, overridden moraines with fluted surfaces, and glaciofluvial outwash. Some of the drumlins extend towards the 1995 end moraine but terminate abruptly at the moraine and are not observed in front of it. This suggests that they were formed sub-marginally during the 1966–1995 terminal position. The sedimentary structure of the drumlins is best explained by the sticky spot model. Dating and dendrochronological analyses of birch logs found on the surface of one of the drumlins indicate that the valley was forested about 2100 calendar year BP, after which the glacier started to reform, possibly due to an abrupt change in climate.